2015
DOI: 10.2166/wst.2015.031
|View full text |Cite
|
Sign up to set email alerts
|

N-methyl-2-pyrrolidone-degrading bacteria from activated sludge

Abstract: N-methyl-2-pyrrolidone (NMP) is a widely used solvent for many organic compounds and a component found in a vast array of chemical preparations. For this research paper, NMP degrading bacteria were isolated from two samples of activated sludge. They pertained to both Gram-negative and Gram-positive members, and belong to the Pseudomonas, Paracoccus, Acinetobacter and Rhodococcus genera. All the strains utilized 300 mg/L of NMP as the only source of carbon, energy and nitrogen over several days, and they were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The process water mainly contained NMP (1500-1600 mg/L), LiCl (0-150 mg/L) and polyethylene glycol (PEG) (0-800 mg/L), in which NMP accounted for ~90% of organic substances on average. The minerals were supplemented into the feed water, including K2HPO4 (0.18 g/L), Na2HPO4•12H2O (1.92 g/L), MgSO4•7H2O (0.1 g/L), FeSO4•7H2O (0.01 g/L), CaCl2 (0.01 g/L), and NaCl (0.5 g/L) [2].…”
Section: Nmp-containing Process Wastewatermentioning
confidence: 99%
See 3 more Smart Citations
“…The process water mainly contained NMP (1500-1600 mg/L), LiCl (0-150 mg/L) and polyethylene glycol (PEG) (0-800 mg/L), in which NMP accounted for ~90% of organic substances on average. The minerals were supplemented into the feed water, including K2HPO4 (0.18 g/L), Na2HPO4•12H2O (1.92 g/L), MgSO4•7H2O (0.1 g/L), FeSO4•7H2O (0.01 g/L), CaCl2 (0.01 g/L), and NaCl (0.5 g/L) [2].…”
Section: Nmp-containing Process Wastewatermentioning
confidence: 99%
“…However, our findings revealed that SBR was more feasible than MBR to treat the high-strength NMP-containing wastewater. In previous studies, NMP had proven to be readily biodegraded by air-dried activated sludge [1] or pure cultures (such as Pseudomonas, Paracoccus, Acinetobacter and Rhodococcus) isolated from the activated sludge [2,8]. Therefore, the high biodegradability of NMP compounds guarantees no shock loading to the SBR in treating high strength NMP-containing wastewater.…”
Section: Figure 1 Ph and Conductivity Of The Feed And Reactor Effluentmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the polymer of N , N ’-dimethylene-bis(pyrrolidone-4-carboxylic acid) (BP-C 2 ) and 1,6-hexanediol with a glass transition temperature of 24 °C and a M w of 78 kg/mol is reported to hydrolyze fully upon immersion in water for one year ( M w of 688 g/mol) [18]. Given the biodegradability of the structurally similar n-methyl pyrrolidone (NMP), BPDAs might also be biodegraded by bacteria belonging to the Pseudomonas , Paracoccus , Acinetobacter , and Rhodococcus genera existing in sewage [27,28,29]. However, we would like to stress that as the biodegradability of these monomers is not confirmed, this remains a point for future investigations.…”
Section: Introductionmentioning
confidence: 99%